Preschool teachers' implementation of evidence-based practices for children with autism spectrum disorder: an investigative study - Mohammed Akram Hamdan; Mohammed Hasan Ali Al-Abyadh (CV. Literasi Indonesia, 2026)
The study explored preschool teachers’ evidence-based practices when teaching students diagnosed with autism spectrum disorder (ASD). The sample included 76 preschool teachers from different regions of the Kingdom of Saudi Arabia (KSA), including Tabuk, Eastern Province, Makkah Al-Mukarramah, Riyadh, and Asir, who teach in inclusive classrooms with students with ASD. The primary instrument was a 28-item, structured questionnaire designed to assess the extent of teachers’ implementation of evidence-based practices (EBPs). The results showed that the total degree of the sample teachers’ evidence-based practices was moderate. Positive reinforcement was the most used practice, while antecedent-based interventions and behavioral momentum (high-probability request sequence) interventions were the least used. In addition, no significant differences were observed in teachers’ evidence-based practices with ASD students due to the duration of years of teaching experience and academic qualifications at the 0.05 significance level. Teachers need to be provided with more focused in-service training that increases teachers' professional development to improve their knowledge and skills. The study confirms the existing research gap on the utilization of EBPs in early childhood education and offers data-based insights to policymakers and practitioners in inclusive education.